Meta-Analysis: Amniotic Meconium and Low Birth Weight as Predictors of Asphyxia in Newborns - Widiyaningrum, Alfiati Nanda; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Preterm birth, intrapartum-related complications (birth asphyxia or diffi